THE ROLE OF CIVIL SOCIETY IN BUILDING SOCIAL HARMONY IN THE MIDST OF CULTURAL DIVERSITY - Zaenal Abidin (Tahta Media Group, 2025)
This study aims to analyze the role, challenges, and opportunities of civil society in fostering social harmony within multicultural societies. The research employs a qualitative approach with a socio-legal design and multiple case studies involving several civil society organizations operating in culturally diverse regions. Data were collected through in-depth interviews, participant observation, and document analysis of organizational reports and related policies. The findings reveal that civil society plays a crucial role as a facilitator of intergroup dialogue, a promoter of multicultural education, a mediator of social conflicts, and an advocate for inclusive public policies. Community dialogue programs, digital literacy initiatives, and interfaith collaborations have contributed to strengthening social trust and reducing intergroup prejudice. Nevertheless, efforts to build social harmony face significant challenges, including identity polarization, digital misinformation, socio-economic inequality, limited organizational capacity, and uneven policy support. Conversely, growing youth openness, constructive use of digital technology, cross-community networking, and policy initiatives promoting religious moderation present valuable opportunities. The study concludes that social harmony is a continuous process requiring multidimensional strategies and collaboration among civil society, government institutions, and local communities to ensure inclusive and sustainable social cohesion.